A Comprehensive Review of Health Benefits of Qigong and Tai Chi - Jahnke, Roger; Larkey, Linda; Rogers, Carol; Etnier, Jennifer; Lin, Fang (American journal of health promotion, 2010)
Objective. Research examining psychological and physiological benefits of Qigong and Tai Chi is growing rapidly. The many practices described as Qigong or Tai Chi have similar theoretical roots, proposed mechanisms of action, and expected benefits. Research trials and reviews, however, treat them as separate targets of examination. This review examines the evidence for achieving outcomes from randomized controlled trials (RCTs) of both. Data Sources. The key words Tai Chi, Taiji, Tai Chi Chuan, and Qigong were entered into electronic search engines for the Cumulative Index for Allied Health and Nursing (CINAHL), psychological literature (PsycINFO), PubMed, Cochrane database, and Google Scholar. Study Inclusion Criteria. RCTs reporting on the results of Qigong or Tai Chi interventions and published in peer-reviewed journals from 1993 to 2007. Data Extraction. Country, type and duration of activity, number/type of subjects, control conditions, and reported outcomes were recorded for each study. Synthesis. Outcomes related to Qigong and Tai Chi practice were identified and evaluated. Results. Seventy-seven articles met the inclusion criteria. The nine outcome category groupings that emerged were bone density (n = 4), cardiopulmonary effects (n = 19), physical function (n = 16), falls and related risk factors (n = 23), quality of life (n = 17), self-efficacy (n = 8), patient-reported outcomes (n = 13), psychological symptoms (n = 27), and immune function (n = 6). Conclusions. Research has demonstrated consistent, significant results for a number of health benefits in RCTs, evidencing progress toward recognizing the similarity and equivalence of Qigong and Tai Chi.